Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/data9010008
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylome and Transcriptome Maps of Primary Colorectal Cancer and Matched Liver Metastasis

Priyadarshana Ajithkumar,
Gregory Gimenez,
Peter A. Stockwell
et al.

Abstract: Sequencing-based genome-wide DNA methylation, gene expression studies and associated data on paired colorectal cancer (CRC) primary and liver metastasis are very limited. We have profiled the DNA methylome and transcriptome of matched primary CRC and liver metastasis samples from the same patients. Genome-scale methylation and expression levels were examined using Reduced Representation Bisulfite Sequencing (RRBS) and RNA-Seq, respectively. To investigate DNA methylation and expression patterns, we generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This approach enabled the simultaneous analysis of DNA methylation patterns and gene expression changes, which provided a multi-dimensional view of the molecular and functional alterations occurring during CRC progression and metastasis to the liver. Using RRBS, a panel of 244 differentially methylated CpGs (DMCs) (68 hypomethylated and 176 hypermethylated) were identified in liver metastatic tissues (n = 10) in comparison to paired (i.e., from the same patients) primary CRC tissues (n = 10) [42,62]. The majority of the 244 DMCs exhibited hypomethylation in the normal colon and primary CRC, which eventually changed to hypermethylation in liver metastasis.…”
Section: Dna Hyper and Hypomethylation As An Early Event To Predict L...mentioning
confidence: 99%
See 2 more Smart Citations
“…This approach enabled the simultaneous analysis of DNA methylation patterns and gene expression changes, which provided a multi-dimensional view of the molecular and functional alterations occurring during CRC progression and metastasis to the liver. Using RRBS, a panel of 244 differentially methylated CpGs (DMCs) (68 hypomethylated and 176 hypermethylated) were identified in liver metastatic tissues (n = 10) in comparison to paired (i.e., from the same patients) primary CRC tissues (n = 10) [42,62]. The majority of the 244 DMCs exhibited hypomethylation in the normal colon and primary CRC, which eventually changed to hypermethylation in liver metastasis.…”
Section: Dna Hyper and Hypomethylation As An Early Event To Predict L...mentioning
confidence: 99%
“…The majority of the 244 DMCs exhibited hypomethylation in the normal colon and primary CRC, which eventually changed to hypermethylation in liver metastasis. The integration of methylation data (165 DMCs-genes or regulatory regions) with matched transcriptome data showed that the methylation changes of 21 DMCs were highly correlated with alterations in the expression of 20 protein-coding genes linked to those 21 DMCs (a Spearman or Pearson correlation coefficient < 0.4, p-value < 0.05) [42,62]. These 21 DMCs could possibly be epigenetic drivers of CRC metastasis [42].…”
Section: Dna Hyper and Hypomethylation As An Early Event To Predict L...mentioning
confidence: 99%
See 1 more Smart Citation